Portuguese translation and validation of the questionnaires from the Canadian Physical Literacy Assessment-2: a pilot study - Mendoza-Muñoz, María; Carlos-Vivas, Jorge; Castillo-Paredes, Antonio; Parraca, Jose A.; Raimundo, Armando; Alegrete, Joana; Pastor-Cisneros, Raquel; Gomez-Galan, Rafael (Frontiers in Psychology, 2023)
Background/Objective. This study aimed to translate, and culturally adapt the Canadian Physical Literacy Assessment 2 (CAPL-2) into Portuguese, as well as to test its psychometric properties, in children between 8 and 12 years of age. Methods. The CAPL-2 questionnaires were translated into Portuguese using a translation-back-translation methodology and adapted to its context. The test-retest reliability, internal consistency, and confirmatory factor analysis of the CAPL-2 Portuguese version were analysed in a sample of 69 and 138 students, respectively, from a school in the Alentejo region (Portugal). Results. The Portuguese version of the CAPL-2 questionnaires demonstrated high internal consistency (Cronbach’s α: 0.713 to 0.979) and test-retest reliability ranging from moderate to nearly perfect in the motivation and confidence domain and knowledge and comprehension domain (ICC = 0.549 to 0.932). The results showed a good fit after adjusting for covariation paths (CMIN/DF = 1.382, p = 0.105, RMSEA = 0.053, CFI = 0.971, TLI = 0.955, NFI = 0.907). Conclusion. The Portuguese version of the CAPL-2 questionnaires, after being translated and adapted to the specific context, demonstrated validity and reliability, making them suitable for assessing physical literacy in children aged 8 to 12 years